CUTANEOUS HORNS - Raziq, Fazle; Qayum, Iftikhar; Wahid, Abdul (Journal of Ayub Medical College Abbottabad, 1995)
Cutaneous horn is a rare and curious clinical entity. It is a clinical term used for a hard and elongated structure consisting of keratin and growing on the skin like the ones seen on the heads of cows, sheep etc. It is associated with different types of histologic lesions found at the base of the horn. The base should be carefully examined to see for any such lesion which may include malignancy as well.